Characterization of producers and quinoa supply chains in the Peruvian regions of Puno and Junin - Mercado, Waldemar (2017)
The present study aims to categorize quinoa producers and examine and compare quinoa supply chains in the Peruvian regions of Puno and Junin. This research was conducted in the provinces of San Roman and El Collao in Puno and Jauja and Huancayo in Junin using surveys of producers selected according to stratified sampling, along with interviews and workshops with traders and agents in the supply chain. Cluster analysis was used to examine the producers’ attributes, the supply chain, and the profit margins of conventional and organic producers. In both regions, most producers were small and medium sized (100% in Puno and 91.6% in Junin). The supply chains in Puno and Junin comprised 24 and 31 channels, respectively. It was found that numerous collectors, formal and informal processors, and exporters mainly linked with organized producers participated in these supply chains and this made trade efficient and coordinated. In contrast, trade among individual producers in the domestic markets through agents in the supply chain was highly disjointed, tending toward high centralization and without added value. It is concluded that quinoa supply is complex, centralized, traditional, and somewhat inefficient since asymmetrical relations were found between agents favoring commercial intermediaries.